Diagnosing The Dynamic Drivers of Healthcare Expenditure in Organisation of Islamic Cooperation (OIC) Countries - Wahab, Abdul Azeez Oluwanisola Abdul; Hashim, Nurhazirah; Kefeli, Zurina (Journal of Reviews on Global Economics, 2019)
The foremost impact of healthcare system is for the individuals to have the right and privileges to access enhanced healthcare services. The demand for health, innovation and sustainable healthcare systems has also been gaining better prominence and consideration in numerous countries, and it is perceived as one of the major contributors to the economic growth and development. This paper looks at the dynamic drivers of healthcare expenditure in Organisation of Islamic Cooperation (OIC) countries from 1990 to 2015. The dynamic panel system Generalized Method of Moments (GMM) technique was used for the study analysis. The findings show that the income, life expectancy, share of population between the age group of 65 years and above, share of population age under 15 years, out-of-pocket payment, research and development (technology) in healthcare and consumer price index were the drivers of healthcare expenditure in OIC countries. In view of this, the study differs from recent and previous studies, because the study offers novel empirical findings as the income per capita is above one, which is about 1.90 and inelastic. This proves that healthcare in OIC countries is a luxury goods.